Investigating Principles and Models of Curriculum Development in some Iraqi Kurdistan Regional Universities through Teachers’ Point of View - عمر، تازان كمال; عباس، عباس مصطفى (جامعة تكريت - كلية التربية للبنات, 2023)
هذه الدراسة عبارة عن مقالة مستلة من أطروحة دكتوراه تتعلق بالمنهج الدراسي الذي يعتبر أحد المكونات الرئيسية لبرنامج ناجح على وجه التحديد في مجال تدريس اللغة الإنجليزية. بشأن تدريس أهم المعلومات للمتعلمين في مجالهم. يتكون المنهج الدراسي ككل من مرحلة تطوير البرامج وكيفية تصميمها. إنها تعمل كخطة معدة بناء على المعايير التي توجه تعليمات الفصل وكيف ينبغي تقييمها. علاوة على ذلك، يعد تطوير المناهج عملية منهجية تحاول تنظيم والإجابة على أسئلة ماذا ومن وكيف سيتم تدريس شيء ما للمتعلمين وتتعلق منظمة المناهج بترتيبات وأنماط مكونات المناهج الدراسية التي يتم تنظيمها في موضوعات ودروس ووحدات والموضوعات والدورات بغرض مساعدة المتعلمين على فهم المواد بشكل أكبر وتحقيق الأهداف الأكاديمية. توفر ورقة تصميم البحث الكمي هذه المعلومات الضرورية والأكثر أهمية حول نماذج ومبادئ تطوير المناهج والمناهج في نطاق تدريس اللغة الإنجليزية. تؤخذ جامعات السليمانية وصلاح الدين ودهوك بعين الاعتبار كنماذج من الدراسة. لهذا الغرض، تم جمع البيانات من 33 مدرسا جامعيا في جامعات السليمانية وصلاح الدين ودهوك. الاستبيان لديه موثوقية 0.83 كرونباخ الفا. تظهر نتائج الدراسة المستندة إلى وجهة نظر المعلمين أن الطلبة أهدافهم إلى أن يصبحوا معلمين وأنهم على دراية بأهداف الدورات وأهدافها ويستخدمون اللغة الإنجليزية في معظم الأوقات. يعلنون أيضا أن النهج الذي يركز على الطالب مستخدم ولا توجد موارد كافية لتنفيذ البرنامج كما هو مطلوب. يكشف المعلمون أيضا عن أن الدورات التدريبية مرتبة من بسيطة إلى معقدة لكنهم ليسوا على دراية كافية بالطريقة التي يتم اتباعها للحصول على البرنامج الحالي. This study is an extracted paper from a PhD dissertation that relates to curriculum which is considered as one of the major components of a successful program specifically in the field of English language teaching. Concerning teaching the most important information for learners in their arena. Curriculum as a whole procedure consists of development stage of programs and how it should be designed. It works as a prepared plan based on standards that guides the class instructions and how it should be assessed. Furthermore, Curriculum development is a systematic process that tries to organize and answer the questions of what, who and how something will be taught for learners and curriculum organization relates to arrangements and patterns of the components of curriculum which are organized into topics, lessons, units, subjects and courses for the purpose of helping learners to understand the materials more and achieve the academic goals. This quantitative research design paper provides the most necessary and significant information about the models and principles of curriculum and curriculum development in the scope of ELT in KRG. The universities of Sulaimani, Salahaddin, and Duhok is taken into consideration as samples of the study. For this purpose, the data has been collected from 33 university teachers at universities of Sulaimani, Salahaddin, and Duhok. The questionnaire has reliability of 0.83 Cronbach Alpha. Findings of the study based on the teachers’ point of view show that the students are aimed at to become teachers and they are aware about the goals and objectives of courses and they do use English most of the time. They also declare that the studentcentered approach is used and there are not enough resources to implement the program as it is required to. The teachers’ also reveal that the courses arranged from simple to complex but they are not aware enough which approach is followed to have the current program.
Keywords: التطوير التعليمي -- الجامعات العراقية -- المناهج الدراسية -- تدريس اللغة الإنجليزية -- الدورات التدريبية